Specifics of chronic fatigue syndrome coping strategies identified in a French flash survey during the COVID‐19 containment. (6th April 2021) - Moncorps, Florence; Jouet, Emmanuelle; Bayen, Sabine; Fornasieri, Isabelle; Renet, Sophie; Las‐Vergnas, Olivier; Messaadi, Nassir
Abstract: The COVID‐19 pandemic has focused health systems on supporting patients affected by this virus. Meanwhile in the community, many other contained patients could only use self‐care strategies, especially in countries that have set up a long and strict containment such as France. The study aimed to compare coping strategies deployed by patients with Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS; a poorly recognised syndrome) to those with better known and referenced chronic conditions. An online flash survey was conducted during the containment period in partnership with French Patients Organizations including ME/CFS national association. Therefore, 'Brief COPE' version of Lazarus and Folkman's Ways of Coping Check List has been adapted to the specificity of the containment. The survey was e‐distributed in France from 15 April to 11 May 2020. Differences of coping strategies were analyzed using Wilcoxon–Mann–Withney test. Amongst 637 responses, 192 were complete, presenting a wide variety of diseases, including 93 ME/CFS. The latter have significantly different coping strategies than recognised diagnosed diseases patients: similar uses of emotion focused coping but less uses of seek social support and problem‐focused copings. In conclusion, coping strategies are different for those who deal with the daily experience of ME/CFS, highly disabling chronic condition with diagnostic ambiguity, low degree of medical and social recognition and without treatment. Better understanding of those strategies is needed to provide the means for health promotion researchers, managers and clinicians, to accompany those patients.